DESIGNING A BASIC DIGITAL TRACEABILITY FLOW MODEL SHARIA-BASED IN THE HALAL INDUSTRY SUPPLY CHAIN - Muhammad Hafizh Al Harits; Rizqi Bagus Pratama; Ahmad Muhammad Adam (REVENUE: Jurnal Manajemen Bisnis Islam, 2026)
This study aims to design a basic digital traceability flow model aligned with Islamic Sharia principles within the halal industry supply chain, focusing on the animal slaughter sector at Slaughterhouses (RPH). The lack of transparent information regarding animal origin, slaughter processes, and meat distribution to consumers forms the background that drives the urgency of this research. The method used is mixed methods, combining a qualitative approach through direct observation at the RPH with a quantitative approach via questionnaires distributed to 30 respondents consisting of consumers and meat business operators. Field observation results indicate that the process at the RPH located in the Pekalongan region has met Sharia procedures in practice, but has not yet been equipped with a digital documentation system accessible to consumers. Questionnaire results show an average satisfaction score for halal information transparency needs of 4.18 out of 5, with 83.5% of respondents agreeing or strongly agreeing with the importance of supply chain information digitalization. The designed digital flow model covers four main stages: animal identification, Sharia verification, processing, and QR Code-based distribution. The system has not been fully implemented, but conceptual testing shows great potential in enhancing consumer trust in the halal status of products.   Keywords: digital traceability, halal supply chain, Sharia, slaughterhouse, information transparency, QR Code